Subtractive Protein Profiling of Salmonella typhimurium Biofilm Treated with DMSO - Yahya, Mohd Fakharul Zaman Raja; Alias, Zazali; Karsani, Saiful Anuar (Springer Verlag, 2017)
Salmonellatyphimurium is an important biofilm-forming bacteria. It is known to be resistant to a wide range of antimicrobials. The present study was carried out to evaluate the effects of dimethyl sulfoxide (DMSO) against S. typhimurium biofilm and investigate whole-cell protein expression by biofilm cells following treatment with DMSO. Antibiofilm activities were assessed using pellicle assay, crystal violet assay, colony-forming unit counting and extracellular polymeric substance (EPS) matrix assay whilst differential protein expression was investigated using a combination of one dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis, tandem mass spectrometry and bioinformatics. Treatment with 32% DMSO inhibited pellicle formation, biofilm viability, biofilm biomass and several important components of EPS matrix. Subtractive protein profiling identified two unique protein bands (25.4 and 51.2 kDa) which were present only in control biofilm and not in 32% DMSO-treated biofilm. In turn, 29 and 46 proteins were successfully identified from the protein bands of 25.4 and 51.2 kDa respectively. Protein interaction network analysis identified several biological pathways to be affected, including glycolysis, PhoP–PhoQ phosphorelay signalling and flagellar biosynthesis. The present study suggests that DMSO may inhibit multiple biological pathways to control biofilm formation.